2006
DOI: 10.1093/ije/dyl160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socioeconomic change from birth to early adulthood on height and overweight

Abstract: Socioeconomic trajectories affected both height and overweight, the effect on the latter being different for each gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 16 publications
4
73
1
4
Order By: Relevance
“…Brazilian studies found a direct association between childhood socioeconomic status and BMI in late adolescence and early adulthood in men 24,25 , and an inverse association in women 44 . Thus, although the results of cross-sectional studies are subject to reverse causality -whereby obesity can determine current socioeconomic status rather than vice-versa 4,6,8,28,30 -, the transition process described above is consistent with our finding of clearer associations in women than in men for the effects of early poverty.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Brazilian studies found a direct association between childhood socioeconomic status and BMI in late adolescence and early adulthood in men 24,25 , and an inverse association in women 44 . Thus, although the results of cross-sectional studies are subject to reverse causality -whereby obesity can determine current socioeconomic status rather than vice-versa 4,6,8,28,30 -, the transition process described above is consistent with our finding of clearer associations in women than in men for the effects of early poverty.…”
Section: Discussionmentioning
confidence: 91%
“…Nearly all studies on the association between socioeconomic status and obesity in adults have a cross-sectional design, in which both variables are measured simultaneously 4,6,8,23 . By reviewing the literature, we found 40 studies evaluating the relationship between childhood socioeconomic status and obesity in adulthood, of which only three were conducted in medium or low-income countries: two in Brazil 24,25 and one in China 26 . There are even fewer articles specifically evaluating the association between socioeconomic status and abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Matijasevich et al (28) , who studied the trends in socio-economic inequalities and their effect on overweight prevalence The highest degree of upward mobility among those in the lower economic classes in the present study is similar to that observed in other studies using criteria other than the 'Brazil criterion' used here. For example, in the Pelotas birth cohort, subjects were observed up to the age of 19 years and were classified by family income level (11) . Further, national data show the same trend and that in 2011 Brazil reached the lowest level of economic inequality in its history (9) , mainly due to the government-sponsored Bolsa Família cash transfer programme.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood growth, a strong predictor of adult height, is strongly determined by good nutrition and living conditions in utero and during childhood (Peck and Lundberg 1995;Li et al 2004;Barros et al 2006;Ehounoux et al 2009). On average, a man from the study birth cohorts (born between 1937 and 1948) who had good nutrition and living conditions in utero and during childhood should have attained higher stature than a man who had poor nutrition and living conditions during early life.…”
Section: Main Findingsmentioning
confidence: 99%